Health-related quality of life in patients undergoing hemodialysis - Miljanović Gora; Marjanović Milan; Radaković Sonja; Janošević Miljojko; Mraović Tatjana; Rađen Slavica (Vojnosanitetski Pregled, 2018)
Background/Aim. Chronic renal disease is one of the growing problems all over the world. Health-related quality of life (HRQoL) is an important indicator for those with a chronic disease, such as chronic renal disease, because it may serve as predictor of mortality and hospitalization. The aim of this study was to assess HRQoL in patients on chronic maintenance hemodialysis (HD), and compare it with patients suffering from hypertension (HTA), and normal controls of the same age and gender (C). Methods. The study enrolled 224 males and females older than 18 years: 67 in the HD group, 78 in the HTA group, and 79 in the C group. HRQoL was assessed in all groups using 15-D questionnaire. Results. Significantly higher level of education was recorded in the HD group compared to other two groups. In the HD group there were significantly less employed persons (9%) and significantly more retired (67.2%). All groups were similar regarding an average monthly income and marital status. We found significantly lower total HRQoL score in patients in the HD group, compared to normal controls (0.78 ± 0.16 vs. 0.89 ± 0.10 in the HTA and 0.95 ± 0.06 in the C group) as well as specific scores in almost all investigated domains, except in speech, eating and mental functions. Patients in the HD and HTA groups had similar self-reported quality of life in additional 3 domains: hearing, elimination and distress, while the HD group reported significantly lower scores in remaining 9 domains: mobility, vision, breathing, sleeping, usual activities, discomfort and symptoms, depression, vitality and sexual activity. Patients in the HTA group had significantly lower scores than normal controls in 8 domains (hearing, sleeping, elimination, usual activities, discomfort and symptoms, depression, distress and vitality) as well as in total quality of life, while in remaining 4 domains there was no significant difference (mobility, vision, breathing, sexual activity). Conclusion. Both investigated chronic diseases lead to impairment of HRQoL, which is substantially stronger in hemodialysis than in hypertension. Considering the relationship between depression and HRQoL measures, it may be useful to treat depression of HD patients in order to improve their quality of life.